Synthesis and Activation Study of Iron (Fe) Based Fischer Tropsch (FT) Catalyst Using Sol-gel Method - Muchammad Zainul Anwar; Rachmat Triandi Tjahjanto; Uswatun Hasanah (Chemistry Department, The University of Brawijaya, 2019)
As oil consumption increases from year to year, efforts need to be made to increase energy reserves by developing new renewable energy. One way to develop energy sources is by the synthesis Fischer Tropsch (FT). FT is a synthetic gas conversion reaction (mixture of CO and H2) into a long chain hydrocarbon mixture. The FT reaction requires a catalyst called the FT catalyst. So far, many studies that examine the effectiveness of catalysts in converting synthesis gas into long chain hydrocarbons, but rarely information about the composition of the phases that exist on the surface of the catalyst. To study about it, we synthesized FT catalysts at various variations of calcination temperature. Fe(NO3)3 as a precursor and Cu(NO3)2 as promoter (20:1) used in this study. The calcination temperature used are 300, 500, and 700°C. Characterization and analysis of catalysts were formed with XRD and SEM-EDX. Calcined catalysts were activated using CO2 and H2 gas and then re-characterized with XRD and SEM-EDX. Calcination results the formation of an iron oxide phase, while activation results the formation of iron carbide and zero Fe phases.